Effect of Fragrant Primula Flowers on Physiology and Psychology in Female College Students: An Empirical Study - Jiang, Songlin; Deng, Li; Luo, Hao; Li, Xi; Guo, Baimeng; Jiang, Mingyan; Jia, Yin; Ma, Jun; Sun, Lingxia; Huang, Zhuo (Frontiers in Psychology, 2021)
Indoor plants can positively impact physical and mental health in daily life. However, the benefits of viewing indoor plants may be enhanced if the plants emit a fragrant aroma. In this crossover-design study, we measured the physiological and psychological effects of fragrant and non-fragrant Primula plants on 50 female college students, and explored whether aroma stimulation had additive benefits for this group. Non-fragrant Primula malacoides Franch was used as a control stimulus, and Primula forbesii Franch, which has a floral fragrance, was used as an experimental stimulus. We measured blood pressure, pulse rate, and EEG to evaluate physiological responses, and used a mood state profile and the semantic differential method to evaluate psychological responses. We found that mean blood pressure and pulse rate decreased significantly after the experiment in both conditions. EEGs showed that the mean values of high alpha waves, high beta waves, and relaxation scores were significantly higher in the experimental vs. control condition. The average scores on each subscale of the psychological questionnaire improved after the experiment in both conditions, and the vitality subscale and total emotional state scores were significantly better in the experimental vs. control condition. The results of the semantic differential method showed that the sense of relaxation and comfort were significantly higher in the experimental vs. control condition. Compared with the non-fragrant Primula, the fragrant Primula induced relatively better physiological and psychological effects.